Modified sodium ion battery positive electrode material and preparation method thereof, sodium ion battery
By coating the surface of the positive electrode material of sodium ion battery, the problem of structural collapse of the material during sodium storage is solved, and the cycle life and electrical performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411480441.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The layered oxide positive electrode material of sodium ion battery is prone to phase change and structural collapse during sodium storage, resulting in rapid attenuation of capacity and decreased cycle life.
Titanium nitrogen chloride @ titanium nitride is used as the coating layer to coat and modify the positive electrode material of the sodium ion battery. By depositing titanium nitrogen chloride in situ on the surface of the positive electrode material and heat treatment, a dense cladding layer is formed.
The structural stability and electrical performance of the positive electrode material of sodium ion battery are significantly improved, the capacity attenuation is reduced, and the cycle life of the battery is improved.
Smart Images

Figure CN119008919B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and particularly relates to coating modification of sodium ion battery positive electrode materials. Background Art
[0002] In recent years, sodium-ion batteries have been considered as a new generation of ideal energy storage materials due to their abundant resources and wide distribution. At present, layered oxide cathode materials for sodium-ion batteries have the advantages of large specific capacity, simple synthesis, and low cost, and are an ideal cathode material for sodium-ion batteries. However, layered oxide cathode materials for sodium-ion batteries are prone to phase change during the sodium storage process. Due to the large ionic radius of sodium ions, during the charge and discharge process, as sodium ions are deintercalated, the material structure is prone to collapse, resulting in rapid attenuation of the material capacity and a decrease in the cycle life, which seriously hinders its practical application.
[0003] In response to the above defects, strategies such as doping and coating are currently often used to improve these problems. Summary of the invention
[0004] In response to the above technical problems, the present application provides a modified sodium ion battery positive electrode material and a preparation method thereof, and a sodium ion battery.
[0005] To achieve the above objectives, this application proposes the following technical solutions:
[0006] In a first aspect, a modified sodium ion battery positive electrode material is provided, comprising a sodium ion battery positive electrode material substrate and a coating layer located on at least a portion of the surface of the substrate, wherein the coating layer is titanium chloronitride@titanium nitride.
[0007] Preferably, the chemical formula of the sodium ion battery cathode material matrix is NaTMO 2 , wherein TM is one or more of Ni, Fe, Mn, Co, Cu, Al, and Cr.
[0008] Preferably, the mass of the coating layer is 1-10% of the mass of the sodium ion battery positive electrode material matrix.
[0009] In a second aspect, a method for preparing a modified sodium ion battery positive electrode material is provided, comprising:
[0010] S1. Grinding and mixing a sodium ion battery cathode material and titanium tetrachloride under a protective atmosphere to obtain a mixture;
[0011] S2. Introducing ammonia into a reaction furnace containing the mixture under a protective atmosphere, and sequentially performing a first heat treatment and a second heat treatment to obtain a modified sodium ion battery positive electrode material.
[0012] In some preferred embodiments, the chemical formula of the sodium ion battery positive electrode material is NaTMO 2, wherein TM is one or more of Ni, Fe, Mn, Co, Cu, Al, and Cr.
[0013] In some preferred embodiments, in step S2, the temperature of the first heat treatment is 300-350° C., and the time of the first heat treatment is 4-8 hours.
[0014] In some preferred embodiments, in step S2, the temperature of the second heat treatment is 650-750° C., and the time of the second heat treatment is 2-5 hours.
[0015] In some preferred embodiments, in step S1, the mass ratio of the sodium ion battery positive electrode material to titanium tetrachloride is 50:(1-10).
[0016] In some preferred embodiments, in step S2, the flow rate of ammonia gas is 10-100 mL / min.
[0017] In some preferred embodiments, in step S1 and step S2, the protective atmosphere is a nitrogen atmosphere or an inert gas atmosphere.
[0018] In some preferred embodiments, in step S2, the step of introducing ammonia into the reaction furnace containing the mixture under a protective atmosphere and sequentially performing the first heat treatment and the second heat treatment comprises: introducing a protective gas or a mixture of a protective gas and ammonia into the reaction furnace containing the mixture to expel the air, and then continuously introducing a mixture of a protective gas and ammonia into the reaction furnace, and sequentially performing the first heat treatment and the second heat treatment.
[0019] In a third aspect, a sodium ion battery is provided, comprising the aforementioned modified sodium ion battery positive electrode material or the modified sodium ion battery positive electrode material prepared by the aforementioned preparation method.
[0020] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects:
[0021] The modified positive electrode material provided uses a titanium nitride chloride @ titanium nitride coating layer to coat and modify the sodium ion battery positive electrode material, which can significantly improve the structural stability and electrical properties of the sodium ion battery positive electrode material, reduce capacity attenuation, and increase the cycle life of the battery.
[0022] In-situ coating modification can ensure that the coating layer material is more densely bonded to the material surface, thereby further improving the problems of poor structural stability and rapid capacity decay of the positive electrode material of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 This is the SEM image of the modified positive electrode material prepared in Example 1.
[0025] Figure 2 The cycle performance diagram of button batteries assembled in Examples 1 to 3 and Comparative Examples 1 to 3. DETAILED DESCRIPTION
[0026] The applicant has found through research that coating the surface of the sodium ion battery positive electrode material matrix with titanium nitride chloride @ titanium nitride material can significantly improve the structural stability and electrical properties of the sodium ion battery positive electrode material, reduce capacity attenuation, and increase the cycle life of the battery. Based on this, the present invention has been completed.
[0027] The present invention provides a modified sodium ion battery positive electrode material, comprising a sodium ion battery positive electrode material substrate and a coating layer located on at least a portion of the substrate surface, wherein the coating layer is titanium nitride coated with titanium nitride chloride. By coating the surface of the positive electrode material with titanium nitride chloride @ titanium nitride material, titanium nitride chloride is a layered material that can achieve Na + Titanium nitride has high electrical conductivity and excellent structural stability, which can isolate the positive electrode material from the electrolyte reaction and improve the material cycle stability and electrical performance. Composite coating can effectively stabilize the material structure and prevent side reactions between the material and the electrolyte, thereby improving the battery cycle life and capacity.
[0028] In some preferred embodiments, the chemical formula of the sodium ion battery cathode material matrix is NaTMO 2 , wherein TM is one or more of Ni, Fe, Mn, Co, Cu, Al, and Cr.
[0029] In some preferred embodiments, the mass of the coating layer is 1-10% of the mass of the sodium ion battery positive electrode material matrix, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.
[0030] In some preferred embodiments, the coating layer is obtained by first in-situ depositing titanium nitride chloride on the surface of the positive electrode material substrate and then heat treating it. In-situ coating can improve the bonding force between the positive electrode material substrate and the surface coating layer, thereby further improving the structural stability and cycle stability.
[0031] The present invention provides a method for preparing a modified sodium ion battery positive electrode material, comprising:
[0032] S1. Grinding and mixing a sodium ion battery cathode material and titanium tetrachloride under a protective atmosphere to obtain a mixture;
[0033] S2. Introducing ammonia into a reaction furnace containing the mixture under a protective atmosphere, and sequentially performing a first heat treatment and a second heat treatment to obtain a modified sodium ion battery positive electrode material.
[0034] In some preferred embodiments, the chemical formula of the sodium ion battery positive electrode material is NaTMO 2 , wherein TM is one or more of Ni, Fe, Mn, Co, Cu, Al, and Cr.
[0035] In some preferred embodiments, in step S2, the temperature of the first heat treatment is 300-350°C, for example, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, etc., and the time of the first heat treatment is 4-8h, for example, 4h, 5h, 6h, 7h, 8h, etc.
[0036] In some preferred embodiments, in step S2, the temperature of the second heat treatment is 650-750°C, such as 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, etc., and the time of the second heat treatment is 2-5h, such as 2h, 3h, 4h, 5h, etc. The applicant has found through further research that the use of two-stage heat treatment and optimization of the heat treatment temperature are conducive to improving the composition and microstructure of the coating layer, and further improving the chemical stability and high temperature stability of the positive electrode material.
[0037] In some preferred embodiments, in step S1, the mass ratio of the sodium ion battery positive electrode material to titanium tetrachloride is 50:(1-10), for example, 50:1, 50:2, 50:3, 50:4, 50:5, 50:6, 50:7, 50:8, 50:9, 50:10, etc.
[0038] In some preferred embodiments, in step S2, the flow rate of ammonia gas is 10-100 mL / min, for example, 10 mL / min, 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, 90 mL / min, 100 mL / min, etc.
[0039] In some embodiments, in step S1 and step S2, the protective atmosphere may be a conventional protective atmosphere in the art, for example, a nitrogen atmosphere or an inert gas atmosphere (such as argon, helium, etc.).
[0040] In some preferred embodiments, in step S2, the step of introducing ammonia into the reaction furnace containing the mixture under a protective atmosphere and sequentially performing the first heat treatment and the second heat treatment comprises: introducing a protective gas or a mixture of a protective gas and ammonia into the reaction furnace containing the mixture to expel the air, and then continuously introducing a mixture of a protective gas and ammonia into the reaction furnace, and sequentially performing the first heat treatment and the second heat treatment.
[0041] Some embodiments of the present invention provide a sodium ion battery, comprising the aforementioned modified sodium ion battery positive electrode material or the modified sodium ion battery positive electrode material prepared by the aforementioned preparation method.
[0042] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0043] Embodiment 1:
[0044] A method for preparing a modified sodium ion battery positive electrode material, wherein the positive electrode material is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 , including the following steps:
[0045] (1) In an argon environment, 5g of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 The mixture was mixed and ground with 0.5 g of titanium tetrachloride liquid to obtain a mixture.
[0046] (2) The mixture is placed in a calcining boat, and then the calcining boat is placed in a tube furnace. Argon gas is introduced for a period of time to remove the air in the tube furnace, and then the temperature is raised to 340°C and kept for 7 hours. The temperature is further raised to 680°C and kept for 4 hours, and then cooled to room temperature. Argon and ammonia mixed gas (volume ratio 3:1) is introduced throughout the heat treatment, and the ammonia flow rate is 80 mL / min to obtain a sodium ion battery positive electrode material modified by titanium nitride and titanium nitride synergistic coating. The SEM image of the modified sodium ion battery positive electrode material is shown in the figure. Figure 1 shown.
[0047] Embodiment 2:
[0048] Method for preparing modified sodium ion battery positive electrode material, wherein the positive electrode material is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 , including the following steps:
[0049] (1) In an argon environment, 10g of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 The mixture was mixed and ground with 0.2 g of titanium tetrachloride liquid to obtain a mixture.
[0050] (2) The mixture is placed in a firing boat, which is then placed in a tubular furnace. Argon is introduced for a period of time to remove the air in the tubular furnace, and the temperature is raised to 350°C and kept for 8 hours. The temperature is further raised to 650°C and kept for 2 hours. The mixture is cooled to room temperature. Argon and ammonia mixture (volume ratio 3:1) is introduced throughout the heat treatment process, and the ammonia flow rate is 20 mL / min to obtain a sodium ion positive electrode material modified by titanium nitride chloride and titanium nitride synergistic coating.
[0051] Example 3
[0052] A method for preparing a modified sodium ion battery positive electrode material, wherein the positive electrode material is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 , including the following steps:
[0053] (1) In an argon environment, 2g of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 The mixture was mixed and ground with 0.4 g of titanium tetrachloride liquid to obtain a mixture.
[0054] (2) The mixture is placed in a firing boat, which is then placed in a tubular furnace. Argon is introduced for a period of time to remove the air in the tubular furnace, and the temperature is raised to 300°C and kept for 4 hours. The temperature is further raised to 650°C and kept for 2 hours. The mixture is cooled to room temperature. Argon and ammonia mixture (volume ratio 3:1) is introduced throughout the heat treatment process, and the ammonia flow rate is 100 mL / min to obtain a sodium ion positive electrode material modified by titanium nitride chloride and titanium nitride synergistic coating.
[0055] Comparative Example 1
[0056] The difference between this comparative example and Example 1 is that the positive electrode material of the sodium ion battery NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 Not modified by coating.
[0057] Comparative Example 2
[0058] The difference between this comparative example and Example 1 is that in step (2), the temperature is raised to 340° C. and kept for 7 h, and then further raised to 400° C. and kept for 4 h.
[0059] Comparative Example 3
[0060] The only difference between this comparative example and Example 1 is that in step (2), the temperature is raised to 340° C. and maintained for 7 h.
[0061] Assembly of the sodium-ion half-cell:
[0062] The positive electrode materials obtained in the above Examples 1 to 3 and Comparative Examples 1 to 3 were weighed and ground according to the mass ratio of positive electrode material: conductive graphite: PVDF of 8:1:1, and then an appropriate amount of N-methylpyrrolidone (NMP) was added and continued to grind and stir to form a uniform slurry. The slurry was evenly coated on aluminum foil with a mold to a coating thickness of 200 μm, and placed in a drying oven at 90°C for 10 hours, and then cut into discs with a diameter of 12 mm. The disc was used as the positive electrode, the sodium sheet was used as the negative electrode, and the electrolyte composition included lithium salt NaPF 6 and solvent, the lithium salt concentration is 1 mol / L, the solvent is EC:DEC:DMC in a volume ratio of 1:1:1, and the battery is assembled in the glove box in the button battery assembly order.
[0063] Battery performance test:
[0064] The assembled battery was tested for performance. The assembled battery was placed in a LAND2001CT battery test box for charging and discharging. The test was conducted at 25°C and a cycle voltage of 2-4V for 50 cycles. The relationship between the number of cycles and the discharge specific capacity is as follows: Figure 2 shown.
[0065] Depend on Figure 2 It can be seen that the coated modified positive electrode materials prepared in Examples 1 to 3 and Comparative Example 2 have significantly improved cycle stability and electrical performance compared with the battery assembled with the positive electrode material that has not been coated and modified in Comparative Example 1. After analysis, this is because the coating layer material itself has a layered structure that can well realize the deintercalation of Na ions and has good electrical conductivity and structural stability. And compared with the battery assembled with the positive electrode material prepared in Comparative Example 3 and Comparative Example 1, the former has a higher discharge specific capacity. After analysis, this may also be due to the coating layer material itself having a layered structure that can well realize the deintercalation of Na ions and has good electrical conductivity.
[0066] Depend on Figure 2 It can also be seen that compared with Example 1, the cycle performance of the battery assembled with the coated modified positive electrode material prepared in Comparative Example 2 is significantly reduced. After analysis, this may be because the second heat treatment process in the coating process of step (2) in Example 1 is carried out at a higher temperature, and the ratio of the two phases in the generated coating material titanium nitride chloride @ titanium nitride is better, which makes the coating material have better comprehensive performance of thermal stability and conductive performance, so that the modified positive electrode material can significantly improve the cycle performance without significantly reducing the initial discharge specific capacity.
[0067] Depend on Figure 2 It can also be seen that compared with Example 1, the first discharge specific capacity of the battery assembled with the coated modified positive electrode material prepared in Comparative Example 3 is slightly improved, but the cycle performance is significantly reduced. After analysis, this may be because only heat treatment is carried out at 340°C, which may only achieve titanium nitride chloride coating, or a stable titanium nitride chloride @ titanium nitride coating layer is not obtained, resulting in poor cycle performance.
[0068] Depend on Figure 2 It can also be seen that compared with Example 1, the first discharge specific capacity of the battery assembled with the coated modified positive electrode material prepared in Example 3 is higher, but the cycle performance is lower. After analysis, this may be because the coating amount is large, so the discharge specific capacity is significantly improved, but due to the large thickness of the coating layer, the coating layer is difficult to tightly coat the surface of the positive electrode material, and it may easily fall off during the cycle, and the second stage heat treatment time is relatively short, and the titanium nitride layer is thin, resulting in relatively poor cycle stability.
[0069] Depend on Figure 2 It can also be known that compared with Example 1, the first discharge specific capacity and cycle performance of the battery assembled with the coated modified positive electrode material prepared in Example 2 are worse. After analysis, this may be because the coating amount is small, so the first discharge specific capacity is low, and the two-stage heat treatment time period results in a thinner titanium nitride layer, resulting in relatively poor cycle stability.
[0070] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A modified sodium ion battery positive electrode material, characterized in that: It includes a sodium ion battery positive electrode material matrix and a coating layer located on at least a portion of the surface of the matrix, wherein the coating layer is titanium nitride coated with titanium nitride chloride, and the chemical formula of the sodium ion battery positive electrode material matrix is NaTMO2, wherein TM is one or more of Ni, Fe, Mn, Co, Cu, Al, and Cr.
2. The modified sodium ion battery positive electrode material according to claim 1, characterized in that The mass of the coating layer is 1-10% of the mass of the sodium ion battery positive electrode material matrix.
3. The method for preparing the modified sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: include: S1. Grinding and mixing a sodium ion battery cathode material and titanium tetrachloride under a protective atmosphere to obtain a mixture; S2. Introduce ammonia into a reaction furnace containing the mixture under a protective atmosphere, and perform a first heat treatment and a second heat treatment in sequence to obtain a modified sodium ion battery positive electrode material; the temperature of the first heat treatment is 300-350° C., and the temperature of the second heat treatment is 650-750° C.
4. The method for preparing the modified sodium ion battery positive electrode material according to claim 3, characterized in that: In step S2, the first heat treatment time is 4 to 8 hours; In step S2, the second heat treatment time is 2 to 5 hours.
5. The method for preparing the modified sodium ion battery positive electrode material according to claim 3, characterized in that: In step S1, the mass ratio of the sodium ion battery positive electrode material to titanium tetrachloride is 50:(1-10).
6. The method for preparing the modified sodium ion battery positive electrode material according to claim 3, characterized in that: In step S2, the flow rate of ammonia gas is 10-100 mL / min.
7. The method for preparing the modified sodium ion battery positive electrode material according to claim 3, characterized in that: In step S1 and step S2, the protective atmosphere is a nitrogen atmosphere or an inert gas atmosphere.
8. The method for preparing the modified sodium ion battery positive electrode material according to claim 3, characterized in that: In step S2, the step of introducing ammonia into the reaction furnace containing the mixture under a protective atmosphere and sequentially performing the first heat treatment and the second heat treatment comprises: introducing a protective gas or a mixture of a protective gas and ammonia into the reaction furnace containing the mixture to discharge the air, and then continuously introducing a mixture of a protective gas and ammonia into the reaction furnace, and sequentially performing the first heat treatment and the second heat treatment.
9. A sodium ion battery, characterized in that It includes the modified sodium ion battery positive electrode material as described in claim 1 or 2 or the modified sodium ion battery positive electrode material prepared by the preparation method according to any one of claims 3 to 8.
Citation Information
Patent Citations
Surface-modified titanium chloro-nitride electrode material and preparation method thereof
CN114613949A
Sodium battery positive electrode composite material and preparation method thereof
CN116525802A